Thioflavin T Monitoring of Guanine Quadruplex Formation in the rs689-Dependent INS Intron 1 - Ana Lages; Christopher G. Proud; John W. Holloway; Igor Vorechovsky (Elsevier, 2019)
The human proinsulin gene (INS) contains a thymine-to-adenine variant (rs689) located in the 3' splice site (3' ss) recognition motif of the first intron. The adenine at rs689 is strongly associated with type 1 diabetes. By weakening the polypyrimidine tract, the adenine allele reduces the efficiency of intron 1 splicing, which can be ameliorated by antisense oligonucleotides blocking a splicing silencer located upstream of the 3' ss. The silencer is surrounded by guanine-rich tracts that may form guanine quadruplexes (G4s) and modulate the accessibility of the silencer. Here, we employed thioflavin T (ThT) to monitor G4 formation in synthetic DNAs and RNAs derived from INS intron 1. We show that the antisense target is surrounded by ThT-positive segments in each direction, with oligoribonucleotides exhibiting consistently higher fluorescence than their DNA counterparts. The signal was reduced for ThT-positive oligonucleotides that were extended into the silencer, indicating that flanking G4s have a potential to mask target accessibility. Real-time monitoring of ThT fluorescence during INS transcription in vitro revealed a negative correlation with ex vivo splicing activities of corresponding INS constructs. Together, these results provide a better characterization of antisense targets in INS primary transcripts for restorative strategies designed to improve the INS splicing defect associated with type 1 diabetes. Keywords: type 1 diabetes, proinsulin gene, 3' splice site, polymorphism, G quadruplex, transcription